IMPLEMENTASI GAME WORDWALL DALAM PEMBELAJARAN PKN TERHADAP KEDISIPLINAN BELAJAR SISWA KELAS 4 SEKOLAH DASAR - Uswatun Khasanah; Filia Prima Artharina; Joko Sulianto (Universitas Negeri Medan, 2023)
Abstract: This study aims to describe the application of the Wordwall game in Civics learning to shape student learning discipline. This study uses a type of qualitative research by collecting data through observation, interviews, and questionnaires. Qualitative data analysis was carried out including data collection, data reduction, data presentation and conclusions. Efforts are made by utilizing technology as a learning medium. Researchers use learning media Wordwall. Based on the results of research on the implementation of the wordwoll game in Pkn learning in class 4 D SDN Wonotingal Semarang, learning discipline is good. Through the wordwall game, student discipline in attendance, listening to material, and collecting assignments given can be seen and reviewed through a variety of complete features that teachers can use in meaningful learning. The implementation of digital technology wordwall game applications in Civics learning makes learning fun and meaningful through this alternative for teachers to familiarize students with good behavior in complying with regulations, doing things in a timely and orderly manner and forming the disciplinary character of student learning. Keyword: Wordwall, Pkn, Study DisciplineAbstrak: Tujuan penelitian ini untuk mendeskripsikan penerapan game Wordwall dalam pembelajaran Pkn untuk membentuk kedisiplinan belajar siswa. Penelitian ini menggunakan jenis penelitian kualitatif dengan pengambilan data melalui observasi, wawancara, dan angket. Analisis data kualitatif yang dilakukan meliputi pengumpulan data, reduksi data, penyajian data dan kesimpulan. Upaya yang dilakukan dengan memanfaatkan teknologi sebagai media pembelajaran. Peneliti menggunakan media pembelajaran Wordwall. Berdasarkan hasil penelitian implementasi game wordwoll dalam pembelajaran Pkn pada siswa kelas 4 D SDN Wonotingal Semarang kedisiplinan belajar sudah baik. Melalui game wordwall kedisiplinan siswa dalam kehadiran, menyimak materi, serta mengumpulan tugas yang diberikan dapat dilihat dan ditinjau melalui berbagai fitur lengkap yang dapat dimanfaatkan guru dalam pembelajaran yang bermakna. Implementasi teknologi digital aplikasi permainan wordwall pada mata pelajaran Pkn menjadikan pembelajaran yang menyenangkan dan bermakna melalui ini alternatif guru untuk membiasakan siswa berkelakukan baik dalam mematuhi peraturan, melakukan sesuatu dengan tepat waktu dan tertib serta membentuk karakter kedisiplinan belajar siswa.Kata Kunci: Wordwall, Pkn, Kedisiplinan Belajar